BOWEL OBSTRUCTION DUE TO GALLSTONE ILEUS AS A RARE CAUSE OF ACUTE ABDOMEN: CASE REPORT AND LITERATURE REVIEW - Lopes, Felipe; Leme, Laura; Riccomi, Rodrigo; Pastre, Antonio Augusto P.; Pizzolato, Bianca Benelli; Cruz, Victor Mondadori (Seven Editora, 2025)
Gallstone ileus as a cause of acute intestinal obstruction is a rare condition resulting from a complication of a common disease, cholelithiasis. It is caused by the impaction of a gallstone in the gastrointestinal tract, posing a potential life-threatening risk in cases of delayed diagnosis and management. We present the case of a 65-year-old man with gallstone ileus causing intestinal obstruction, treated with a longitudinal enterotomy and removal of the stone from the intestinal loop, followed by an urgent transverse enterorrhaphy, in which the surgical team opted not to manipulate the gallbladder region during the same procedure. Postoperative evolution was satisfactory, and the patient was discharged eight days after admission. This report aims to describe an uncommon event that should be included in the diagnostic repertoire of obstructive abdomen, especially in the current context of increasing cholelithiasis cases. DOI: https://doi.org/10.56238/sevened2025.037-031